2013
DOI: 10.1177/0363546513512779
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic and Prognostic Value of Ultrasonography in Soccer Players With Acute Hamstring Injuries

Abstract: The biceps femoris is the most commonly injured hamstring muscle detected by ultrasound, and more than half of the injuries are intramuscular. Because neither the presence of sonographic findings nor the size of the findings was correlated with time to return to play in injured soccer players, the prognosis of hamstring injuries should not be guided by these findings alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
2
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 29 publications
0
64
2
11
Order By: Relevance
“…Negative US findings were a better prognosis determinant in the Connell et al 8 study, but no difference in prognosis was found between positive and negative US results by Petersen et al 20 The following were found to be negative prognosis factors: cross-sectional area, 8,15 injury outside of the musculotendinous junction, 8 hematoma, 8,15 structural injury, 9 and injury involving the biceps femoris. 8 Connell et al 8 determined that a longer injury on US was a poor prognosis factor, whereas Petersen et al 20 did not observe this association.…”
Section: Synthesis Of Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Negative US findings were a better prognosis determinant in the Connell et al 8 study, but no difference in prognosis was found between positive and negative US results by Petersen et al 20 The following were found to be negative prognosis factors: cross-sectional area, 8,15 injury outside of the musculotendinous junction, 8 hematoma, 8,15 structural injury, 9 and injury involving the biceps femoris. 8 Connell et al 8 determined that a longer injury on US was a poor prognosis factor, whereas Petersen et al 20 did not observe this association.…”
Section: Synthesis Of Resultsmentioning
confidence: 83%
“…Hip ROM (SLR) at 2 days after injury 1 Passive SLR test (within 3 days after injury) 28 Knee flexion strength at 2 days after injury 1 Palpated length of the painful area Location of most pain during palpation 4 Region, length, width, depth, volume, and cross-sectional area (MRI at 2, 10, 21, and 42 days) 3 Length of the injury (MRI at a mean 13 weeks [range, 1-52 weeks]) 4 Length of the injured area (US at 1-10 days after injury) 20 Distance to the ischial tuberosity (MRI at a mean 13 weeks [range, 1-52 weeks]) 4 Individual vs team sports 4 Location of the hamstring injury (MRI within 3 days) 6 Injured area 15,[26][27][28] Age 6,13 Muscle involved (MRI) 7,10,13,26 Injury to the kicking leg vs supporting leg 10 Side (right, left) 13 Single vs double muscle involvement (MRI within 24-72 hours) 11 Previous hamstring injury 11,13 Sex 13 Sport 13 Degree of injury (I, II [clinically graded]) 13 Frequency of physical therapy sessions 17 Positive vs negative US findings 20 Static stretching, isolated progressive hamstring resistance vs progressive agility and trunk stabilization exercise rehabilitation program 24 Progressive agility and trunk stabilization vs progressive running and eccentric strengthening rehabilitation program 25 Injury involving both the muscle belly and musculotendinous junction (MRI within 3 days) 26 Ganglion-like fluid collection (MRI within 3 days) 26 Hemorrhage-like signal intensity (MRI within 3 days) 26 Time taken to ascend stairs without pain 28 Slump test (within 3 days after injury) 28 Active knee extension test (within 3 days after injury) 28…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is agreed that MRI is not a useful tool in the final criteria of RTP, 8,9 but it is very useful in the beginning. 10 Related to sport medicine there are some injuries that have to be surgically treated immediately and if the clinicians are not skilled in interpreting the MRI and clinical symptoms, they will not be able to assure the correct healing of the injury and the final RTP prediction will be inaccurate.…”
Section: A Correct Diagnosismentioning
confidence: 99%